Examination of the link between life stages uncovered the mechanisms by which habitat characteristics affect odonates. Issue 9 (8th September 2017) - Iwai, Noriko; Akasaka, Munemitsu; Kadoya, Taku; Ishida, Shinya; Aoki, Takashi; Higuchi, Shinsuke; Takamura, Noriko
Abstract: The larval and adult stages of amphibious animals are affected by both aquatic and terrestrial habitat characteristics, and each stage also affects the other. However, this link between life stages has been largely overlooked in previous studies. We examined the effect of aquatic and terrestrial habitat characteristics on the diversity of larval and adult odonates, taking into account the link between the two life stages. Species diversity of adult and larval odonates and aquatic plants, as well as patterns of land use, was investigated in 63 irrigation ponds. We created structural equation models, with paths from land use and aquatic plants characteristics to larval and adult stages of odonates, as well as between the two stages, and chose the best model based on the lowest Akaike information criterion. Adult odonates, but not larvae, were affected by aquatic and terrestrial habitat characteristics, suggesting that the former is the key stage for odonate communities. We observed a positive relationship between the diversity of aquatic plants and larval odonates, but this was in fact due to the effects of aquatic plants on adults, which carried over to the larval stage. Our study showed that a consideration of the link between life stages is crucial for a complete understanding of the relationship between habitat characteristics and amphibious animal populations.